Beobachtungen und Gedanken über Bodenzerstörung im europäischen Russland - Floh, Ernst Friedrich (ERDKUNDE, 1954)
The purpose of this paper is to communicate and discuss observations of soil erosion: firstly, in the western region of mixed forest (approximately 28°E, 53°N); secondly, the eastern region of mixed forest (approximately 52°E, 55°40’N); and thirdly, the steppe area round Stalingrad. In addition the reasons for the absence of ovragi and balki (certain types of gullies) in the steppe region of Kamensk-Shakhty-Krasnopolie (approximately 40°E, 47°30’N) are examined. I. A gentle slope which consisted of pleistocene sandy boulder clay, covered by patchy vegetation on fallow, and used for pasture, showed traces of sheet erosion. At a break of slope in the lower part, where the gradient increased to about 10° (the critical angle), the vegetation was badly disturbed and incipient gully erosion had taken place. The gradient curve had already reached a state of equilibrium and the process of erosion was in its final stages since the local base level rises continuously as a result of deposition of the waste material in a fan. This might throw light upon the origin of problematical dry valleys and similar features (e. :g. dellen). II. From the feeding system of two tributary streams of the Kama river, the surface layer of loam, which lies on top of scarcely disturbed Permian sediment, and is occupied by arable and fallow, is being dissected by gullies where slopes reach gradients of 20°—30°. Soil erosion was probably initiated by deforestation which took place at a time when the Volga-Kama river system experienced a rejuvenation of its erosion power as a result of the shrinkage of the Caspian Sea and the consequent lowering of the base level. This is an example of man-produced and morphologically and technically conditioned soil erosion. The case here mentioned appears to be one where soil erosion forced the secular erosion in a particular direction. III. The boulder clay cover and the underlying tertiary strata of the Volga Hills are being dissected from the Volga base level by genuine erosion gullies, ovragi active rain gullies, and balki, ageing rain gullies, i. e. those which have cut back to the watershed, have reached an equilibrium in their gradient, and only occasionally contain water. In describing an erosion gorge and an ovrag the following main points are discussed. 1. The great importance of cracks in the ground, which occur in consequence of dryness, for slope formation (side erosion), and in particular for back cutting. 2. The very frequent link of young erosion features with old trough valley systems. 3. The influence of the recent lowering of the Volga base level and a rejuvenation of the erosion power and the mutual relationships between soil erosion and secular erosion. 4. The particular importance of protective measures against soil erosion, both by means of an appropriate vegetation cover and other devices, in Southern Russia where the climate is possibly turning more humid, i. e. more favourable to forest growth.